(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Depression is a common psychiatric comorbidity in patients with pulmonary tuberculosis (TB) and has significant impacts on the treatment process and patient prognosis. Integrating mental health in TB patients’ care can enhance the psychological and even physical well-being of the patients. Objectives: Assess the utility of integrated mental health services in the treatment of depression among pulmonary TB patients. Study design: A Cross-Sectional Study Place and duration of study. Department Of Psychiatry Qazi Hussain Ahmed Medical Complex Nowshera from 05-jan 2020 to 05-july 2020 Methods: The study carried out was a randomized controlled trial with 200 Tuberculosis patients. Participants were divided into two groups: One group of patients got standard tuberculosis care, while the other group was administered integrated mental health care. The measures included the severity of depression, treatment compliance, and health status at the initial phase, after three months, and after six months. Results: The study revealed that there was a statistically significant difference between the two groups of participants regarding the duration of the treatment with p = 0. 02, phase of the treatment with p = 0. 02, and the type of the treatment with p = 0. 002. At baseline, moderate depression was present in 52. 7% of the participants, and the duration of therapy was less than a month in 37. 7% of the cases. Other demographics did not show any differences in the results obtained. Conclusion: Integrating mental health services enhances early treatment adherence and reduces depression among pulmonary TB patients. These findings are evidence that mental health interventions should be integrated into TB treatment to improve the lives of patients.